Agranulocytosis and cardiac toxicity - serious side effects of clozapine - Krzewicka-Romaniuk, Ewa; Siedlecka, Dagna; Romaniuk, Artur; Micał, Wojciech (Journal of Education, Health and Sport, 2019)
Clozapine is probably the most effective antipsychotic. Treatment with clozapine is proved to decrease frequency of suicidal behavior. It is related to decrease in use of psychoactive substances and decrease in frequency and intensity of aggressive behavior among patients. It decreases the risk of rehospitalization and relapse. However because of serious, potentially fatal side effects like agranulocytosis or cardiac toxicity, use of clozapine is limited to schizophrenia symptoms partially or fully resistant to treatment with other antipsychotic drugs, or accompanied by persistent suicidal or self-injurious behavior.